PENGARUH CITRA DESTINASI, DAN PROMOSI TERHADAP KEPUASAN PENGUNJUNG MELALUI KEPUTUSAN BERKUNJUNG DI LITTLE VENICE BOGOR - Putri Andika; Rivera Pantro Sukma Silitonga (Human Capital Development, 2023)
This study aims to determine the effect of destination image and promotion on visitor satisfaction through visiting decisions. The population in this study were visitors to Little Venice Bogor. The number of samples in this study were 100 respondents using purposive sampling technique. Data validity and trustworthiness have been checked. Methods for analyzing data that combine quantitative and descriptive methods. Analysis using quantitative data is carried out using structural equation modeling (SEM) with smart PLS software. The results showed that destination image had no significant effect on visitor satisfaction, promotion had a significant effect on visitor satisfaction, destination image had a significant effect on visiting decisions, promotion had a significant effect on visiting decisions, destination image had a significant effect on visitor satisfaction through visiting decisions, promotion had a significant effect on visitor satisfaction through visiting decisions, and visiting decisions had a significant effect on visitor satisfaction.